মাটির কাছে মানুষের কাছে - সিরাজ, শাইখ 1956- (ঢাকা : মাওলা ব্রাদার্স, 2009)
Articles on economical prospects of some agricultural and pisciculture products of Bangladesh.
In Bengali.
Keywords: Farm produce -- Bangladesh -- Marketing; Fish culture -- Economic aspects -- Bangladesh; Agriculture and state -- Bangladesh